Super-resolution microscopy of mitochondrial mRNAs - Stefan Stoldt; Frederike Maass; Michael Weber; Sven Dennerlein; Peter Ilgen; Jutta Gärtner; Aysenur Canfes; Sarah V. Schweighofer; Daniel C. Jans; Peter Rehling; Stefan Jakobs (Nature Communications)
Abstract Mitochondria contain their own DNA (mtDNA) and a dedicated gene expression machinery. As the mitochondrial dimensions are close to the diffraction limit of classical light microscopy, the spatial distribution of mitochondrial proteins and in particular of mitochondrial mRNAs remains underexplored. Here, we establish single-molecule fluorescence in situ hybridization (smFISH) combined with STED and MINFLUX super-resolution microscopy (nanoscopy) to visualize individual mitochondrial mRNA molecules and associated proteins. STED nanoscopy reveals the spatial relationships between distinct mRNA species and proteins such as the RNA granule marker GRSF1, demonstrating adaptive changes in mRNA distribution and quantity in challenged mammalian cells and patient-derived cell lines. Notably, STED-smFISH shows the release of mRNAs during apoptosis, while MINFLUX reveals the folding of the mRNAs into variable shapes, as well as their spatial proximity to mitochondrial ribosomes. These protocols are transferable to various cell types and open new avenues for understanding mitochondrial gene regulation in health and disease.